Current situation and influencing factors of disease uncertainty in parents of children with Sturge‒Weber syndrome: a retrospective study - Na Du; Yue Wu; Shanshan Xiong; Hong Ji; Lulu Huang; Wenyi Guo; Changjuan Zeng (BMC, 2023)
Abstract Background Sturge Weber syndrome (SWS), can cause extensive capillary malformations on the face, head, trunk, and other parts of the body, and the eyes can also suffer optic nerve injury. Secondary glaucoma can cause blindness, which has the characteristics of a relatively hidden onset and unclear pathogenesis. The treatment of SWS secondary glaucoma has always been difficult, and due to the characteristics of the disease, there is uncertainty about the long-term efficacy and safety of various treatment methods for such patients. Methods A total of 105 parents of children with SWS completed a self-designed general information questionnaire, a generalized anxiety questionnaire (GAD-7), a patient health questionnaire (PHQ-2), a stress perception scale (PSS-4), a simple coping scale (SCSQ) and a disease-uncertainty scale (PPUS). Results The total uncertainty score of parents of children with SWS was 79.07 ± 13.24, and the average item score was 2.82 ± 0.47. Multiple linear regression analysis revealed that anxiety and simple coping were the main influencing factors of disease uncertainty among parents of children with SWS (P < 0.05). Conclusions Parents of children with SWS exhibit a high level of disease uncertainty. Medical staff should pay attention to the source of parents' disease uncertainty and provide targeted interventions, which are of great importance in reducing parents' disease uncertainty.